Integration of patient safety into educational curricula and continuing professional training - comparison of patient safety competency models - Eloranta, Sini; Ketola, Saara; Ikonen, Tuija (Frontiers Media SA, 2026)
Introduction:
Patient safety is a fundamental component of high-quality healthcare, and integrating its principles into health professional education and continuing professional development is essential for ensuring safe care. This article describes and compares four international patient safety competency models from high-income regions (Australia, Canada, the United Kingdom, the Nordic countries), and the WHO Multi-professional Patient Safety Curriculum Guide and analyzes their similarities and differences. In this descriptive comparative review, the objective is to identify which competency domains each model emphasises, and which competencies are critical for advancing patient safety across healthcare systems.
Methods:
A thematic analysis of the patient safety competency models was conducted, focusing on their core competency domains and identifying the competencies most critical for advancing patient safety across healthcare systems in high-income regions.
Findings:
Common competency domains include safety culture, systems thinking, teamwork, communication, risk management, human factors, and continuous learning. However, there are notable differences: for example, the Nordic framework for knowledge and skills emphasizes technology and preparedness, Australia highlights ethics, and Canada focuses on resourcing.
Discussion:
The comparison of four patient safety competency models in high-income countries, and the WHO Multi-professional Patient Safety Curriculum Guide shows that they share a common set of core domains, providing a strong basis for aligning patient safety education in high-income countries. At the same time, country specific emphases highlight the need for contextual adaptation.